New nematode species and genera (Nematoda: Chromadorea) from cold seeps on Hikurangi Margin, New Zealand - Leduc, Daniel (European Journal of Taxonomy, 2023)
Relatively little is known about the taxonomy and ecology of deep-sea nematode species inhabiting cold seep habitats. The available data show that cold seep nematode communities are typically characterized by low diversity and are often dominated by a single species, although no nematode taxon appears to have a strong association with methane seepage. In July 2019, a research voyage to New Zealand’s Hikurangi Margin provided an opportunity to characterize the nematode species communities of New Zealand cold seeps, which had not been investigated until now. Here, six new species and two new nematode genera of the class Chromadorea are described from macrofauna cores obtained at three seep sites (Mungaroa, Glendhu, and Uruti South) on Hikurangi Margin from 1227 to 2077 m depth. The species described here represent a wide range of feeding groups, ranging from deposit feeders (Linhomoeus pycnocricus sp. nov., Deraionema barbatum gen. et sp. nov.) to microvores (Aulostomonema abyssum gen. et sp. nov., Aegialoalaimus magnus sp. nov.) and epigrowth feeders (Desmodora parapilosa sp. nov.). The diet of Siphonolaimus curtisensillus sp. nov., which is characterized by an unusual stylet-like feeding apparatus, remains to be determined, however the presence of several different feeding modes in the species described here indicates that a range of food sources are exploited by macrofaunal nematodes at the study sites. Desmodora, Linhomoeus, and Aegialoalaimus have been reported from cold seep habitats previously, however no records of Siphonolaimus from cold seeps could be found in the literature. Aulostomonema gen. nov. does not appear to have a close association with seeps, whilst Deraionema gen. nov. appears to be restricted to the centre of the seep sites where methane seepage is likely strongest. Ongoing work on the ecology and distribution of nematode communities at the Hikurangi Margin seep sites will help determine spatial patterns in abundance and species distributions in more detail, including the identification of any species/taxa with affinities with methane seepage.